Way off: The effect of minimum distance regulation on the deployment of wind power - Jan Stede; Nils May (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Several countries and regions have introduced mandatory minimum distances of wind turbines to nearby residential areas, in order to increase public acceptance of wind power. Germany's largest federal state Bavaria introduced such separation distances of ten times the height of new wind turbines in 2014. Here, we provide a novel monthly district-level dataset of construction permits for wind turbines constructed in Germany between 2010 and 2018. We use this dataset to evaluate the causal effect of introducing the Bavarian minimum distance regulation on the issuance of construction permits for wind turbines. We find that permits decreased by up to 90 percent. This decrease is in the same order of magnitude as the reduction of land area available for wind turbines. The results are in line with findings indicating that minimum distances do not increase the public acceptance of wind power, but harm the expansion of onshore wind power.
Keywords: C21; Q42; R14; R15; 330; onshore wind power; minimum distance; separation distance; energy transition; acceptance; panel data; difference in differences; causal inference; event study